Multicomponent supramolecular assembly of p-hydroxybenzoic acid and malonic acid: a deep insight into the formation of selective cocrystals. Issue 34 (13th August 2020) - Yang, Jinyue; Wang, Na; Tian, Beiqian; Ji, Xiongtao; Hou, Baohong; Wang, Ting; Huang, Xin; Su, Junquan; Yang, Zhanao; Hao, Hongxun
Abstract : Insight into the selective cocrystallization between HBA isomers and MA. Abstract : To investigate the effect of positional isomerism on cocrystallization and reveal the role of weak interactions in the formation of cocrystals, experimental characterization complemented with theoretical computations was thoroughly conducted by using p -hydroxybenzoic acid (PHBA), o -hydroxybenzoic acid (OHBA), m -hydroxybenzoic acid (MHBA) and malonic acid (MA) as model compounds. Selective formation of a new cocrystal was discovered between PHBA and MA molecules via several methods, while no cocrystal was formed between OHBA/MHBA and MA molecules. The PHBA–MA cocrystal was thoroughly characterized and analyzed through several solid characterization techniques such as powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) analysis, Fourier transform infrared (FTIR) spectroscopy, single crystal X-ray diffraction (SCXRD), etc. Taking advantage of a myriad of computational modelling techniques, the molecular recognition mechanism which drove the formation of cocrystals was comprehensively investigated and understood at a molecular level. The structural change accompanied by the cocrystal formation could be rationalized by FTIR spectroscopy and electron density variation analysis. Hirshfeld surface (HS) analysis indicated that O–H⋯O hydrogen bonds played a critical role in the formation of this cocrystal. Molecular electrostatic potential (MESP) surface analysis was employed to predict the interaction sites for cocrystallization, which were in good accordance with the experimental results. Moreover, possible reasons for the selective cocrystallization were analyzed and proposed.